(untitled) (Cardiovascular Journal, 2018)
In the 21st century, Rheumatic fever (RF) and Rheumatic heart disease (RHD) are neglected diseases of marginalized communities. Globally, RHD remains the most-common cardiovascular disease in young people aged <25 years. Although RF and RHD have been almost eradicated in areas with established economies, migration from low-income to high-income settings might be responsible for a new burden of RHD in high-income countries. Globally, the prevalence of rheumatic fever (RF) and rheumatic heart disease (RHD) has declined sharply but, in developing countries, RF is still aleading cause of heart disease and, consequently, death in children and young adults. In 2005, it was estimated that over 2.4 million children aged 5-14 years were having RHD globally and 79% of all these cases were from lessdeveloped countries. Cardiovasc. j. 2018; 10(2): 206-211